Manganese-zinc ferrite granulation powder, manganese-zinc ferrite and preparation method and application of manganese-zinc ferrite granulation powder

By optimizing the formula and sintering process of manganese zinc ferrite granulation powder, the problem of magnetic permeability decrease at high frequency is solved, and the material performance with wide frequency high magnetic permeability and high impedance characteristics is achieved.

CN119707472AActive Publication Date: 2025-03-28MA AN SHAN XIN KANG DA CI YE GU FEN YOU XIAN GONG SI
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411859964.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The existing high permeability MnZn ferrite materials have a too fast magnetic permeability drop at high frequencies and cannot meet the needs of wide frequency and high magnetic permeability.

Method used

By optimizing the formula of manganese-zeb ferrite granulation powder, the proportion of ZnO is increased, and nanoscale auxiliary materials such as CaCO3, Co3O4, Nb2O5, V2O5 and other nanoscale auxiliary materials are all within 100nm. In combination with the special sintering process, the material maintains a high magnetic permeability within a wide frequency range.

Benefits of technology

It has achieved the high permeability of manganese-zeb ferrite materials in a wide frequency range, with an initial permeability of >5000 and a 1MHz permeability of >3000, and the impedance characteristics at high frequency are improved, thereby enhancing the anti-electromagnetic interference capability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005192961850000091
    Figure BDA0005192961850000091
Patent Text Reader

Abstract

The invention discloses manganese zinc ferrite granulation powder, manganese zinc ferrite and a preparation method and application thereof, and belongs to the field of magnetic materials. The granulation powder comprises a main material and an auxiliary material, the main material comprises 52-55 mol% of an iron compound, 19-22 mol% of a zinc compound and the balance of a manganese compound in terms of Fe2O3, the particle size of the auxiliary material is within 100 nm, the auxiliary material comprises 200-1000 ppm of CaCO3 in the total weight of the main material, 500-2000 ppm of Co3O4 in the total weight of the main material, 10-20 ppm of Nb2O5 in the total weight of the main material, and 10-20 ppm of V2O5 in the total weight of the main material. Nb2O5 accounts for 100 ppm to 300 ppm of the total weight of the main materials, and V2O5 accounts for 100 ppm to 500 ppm of the total weight of the main materials. The manganese-zinc ferrite is obtained by molding and sintering the granulation powder, and D10, D50 and D90 of crystal grains in a magnetic core of the manganese-zinc ferrite meet the condition that (D90-D10) / D50 is less than or equal to 1.1. The initial magnetic conductivity of the manganese-zinc ferrite is maintained at 5000 or above, the magnetic conductivity at a frequency point of 1 MHz is maintained at 3000 or above, and the manganese-zinc ferrite also has a relatively high impedance characteristic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic materials, and more specifically, relates to a manganese-zinc ferrite granulated powder, manganese-zinc ferrite and a preparation method and application thereof. Background Art

[0002] High permeability MnZn ferrite material is an important branch of MnZn ferrite. Its main characteristic is the initial permeability (μ i ) is high, usually the starting magnetic permeability (μ i ) above 5000 is called high permeability MnZn ferrite. High permeability MnZn ferrite devices are usually used in low flux density environments, where the initial permeability of the material plays a major role. On the one hand, when the initial permeability of the device is high, the same amount of inductance can be obtained with fewer winding turns. The use of high permeability materials can significantly reduce the size of the device. It is generally believed that the volume of the transformer is related to the μ of the material. i 3 / 2 Inversely proportional, when the magnetic permeability doubles, the transformer volume is only 35% of the original. In addition, fewer winding turns can effectively reduce line losses, which is conducive to the miniaturization, lightweight and energy saving of devices.

[0003] However, with the rapid development of electronic information technology, electronic devices are increasingly integrated, high-frequency, and miniaturized, and various electromagnetic interference problems are becoming increasingly serious. Simply pursuing high magnetic permeability can no longer meet the requirements of electronic development. The research on high magnetic permeability MnZn ferrite materials has shifted to comprehensive performance, and the requirements for the performance of high magnetic permeability MnZn ferrite materials are becoming more and more stringent. In addition to high magnetic permeability, the current high magnetic permeability MnZn ferrite also requires μ i The -f curve is flat over a wide frequency range, allowing the material to be used in a wider frequency range; it also has higher impedance characteristics, thereby improving the material's ability to resist electromagnetic interference.

[0004] Although the initial permeability of the existing high permeability 5K materials on the market is almost the same, the permeability decreases rapidly with the increase of frequency. Due to the influence of inductance, the high-frequency impedance is low. With the rapid development of electronic information technology, the market urgently needs a product with both broadband and high permeability.

[0005] After searching, the Chinese patent application number is 201110230602.2, and the application publication date is February 22, 2012. The patent application document discloses a method for manufacturing a wide-band high-conductivity manganese-zinc ferrite core. The ferrite core batching process takes the formula: Fe2O3 53.88mol%, MnO 36.44mol%, ZnO 9.68mol%; before the granulation process, 58ppm of TiO2, MoO3, V2O5, Bi2O3, CaCO3, SiO2, Nb2O5, SnO2, Co2O3, and CuO are added to the pre-sintered powder as additives to improve the frequency characteristics and loss characteristics of the material.

[0006] The Chinese patent application number is 202010993430.3, and the application publication date is December 29, 2020. The patent application document discloses broadband, high permeability, high impedance manganese-zinc ferrite and its preparation method. The manganese-zinc ferrite includes functional components and auxiliary components. The functional components and their amounts are: Fe2O3: 46.5-49.5 mol%, ZnO: 16.5-18.5 mol%, and the balance is MnO. The sum of the molar ratios of the three functional components is 100%; the auxiliary components are Co2O3, SiO2, CaCO3, Nb2O5, V2O5, TiO2, and SnO2.

[0007] In the above-mentioned manganese-zinc ferrite materials, a large number of auxiliary additives are added to achieve high magnetic permeability, and the initial magnetic permeability can reach 4,000 to 5,000, but the magnetic permeability in a wide frequency range is not clearly recorded. There are many types of existing additives, which can effectively improve the initial magnetic permeability, but as the frequency increases, the action mechanism of various types of additives is complex, which often leads to a decrease in magnetic permeability.

[0008] Therefore, in order to have high magnetic permeability in a wide frequency range, it is urgent to develop a manganese zinc ferrite granulated powder, manganese zinc ferrite and a preparation method and application thereof. Summary of the invention

[0009] 1. Problem to be solved

[0010] One of the purposes of the present invention is to provide a manganese-zinc ferrite granulated powder, aiming to optimize the formula and obtain a raw material for preparing a manganese-zinc ferrite with high magnetic permeability under a wide frequency. Another purpose of the present invention is to provide a manganese-zinc ferrite, aiming to solve the problem that the magnetic permeability of existing high magnetic permeability materials decreases too quickly under high frequencies. A preparation method of the above manganese-zinc ferrite is further provided.

[0011] 2. Technical solution

[0012] In order to solve the above problems, the technical solution adopted by the present invention is as follows:

[0013] According to the purpose of the present invention, the first aspect of the present invention provides a manganese-zinc ferrite granulated powder, including a main material and an auxiliary material, the main material is composed of an iron compound, a zinc compound and a manganese compound, the iron compound is 52-55 mol% in terms of Fe2O3 conversion, the zinc compound is 19-22 mol% in terms of ZnO conversion, and the manganese compound is the remainder in terms of MnO conversion, the particle size of the auxiliary material is within 100 nm, and its composition includes four types of CaCO3, Co3O4, Nb2O5, and V2O5, wherein: CaCO3 accounts for 200ppm-1000ppm of the total weight of the main material, Co3O4 accounts for 500ppm-2000ppm of the total weight of the main material, Nb2O5 accounts for 100ppm-300ppm of the total weight of the main material, and V2O5 accounts for 100ppm-500ppm of the total weight of the main material.

[0014] In the case of adopting the above technical scheme, in order to ensure that the material has both high magnetic permeability and broadband characteristics, the applicant first discovered the optimal composition of the main material in the MnZn ferrite, that is, to increase the proportion of ZnO, keep the molar ratio of iron compound and zinc compound in the range of (52-55): (19-22), and then match four auxiliary materials, and the particle size range of the auxiliary materials is within 100nm. On the one hand, there are only four types of auxiliary materials in the present invention. In the prior art, in order to enhance the magnetic permeability of ferrite, more than five auxiliary materials are often selected to be added to the main material, but there are too many types of auxiliary materials, and the complicated mechanism will affect the magnetic permeability at high frequencies, and the added content of the auxiliary materials will only play a substantial role when it reaches a certain range. Too many types of auxiliary materials will either lead to insufficient addition of a single component, and the effect is not great, or the amount of a single additive is enough to cause the total amount of auxiliary materials to be excessive, and the performance of the ferrite will deteriorate. Even if the initial magnetic permeability is high, the magnetic permeability may also decrease rapidly at high frequencies. On the other hand, the particle size of the auxiliary material added by the present invention is within 100nm, because the specific surface area of ​​the auxiliary material is very large when the particle size is within 100nm, and the surface energy is correspondingly very high; at the same time, the surface atoms of the nanoparticles have a large number of unsaturated bonds, have high chemical activity, and are very easy to combine with other atoms to reach a stable state, so adding the nano auxiliary material helps the uniform growth of the grains of the MnZn ferrite material to reach an ideal size. In addition, since the particle radius of the nano auxiliary material is very small, the same weight of the same impurities, the volume of the nano auxiliary material is larger, and it is easier to be evenly dispersed in the ferrite material, and it is also helpful for the uniform growth of the grains, so adding the nano-level auxiliary material can obtain a high-quality MnZn ferrite material with uniform grains.

[0015] As a possible implementation solution, the weight ratio of CaCO3, Co3O4, Nb2O5 and V2O5 in the auxiliary materials is 8:16:4:3.

[0016] As a possible implementation solution, in the main material, the molar ratio of Fe2O3 and ZnO is 21:8.

[0017] The second aspect of the present invention provides a method for preparing manganese-zinc ferrite granulated powder, comprising the following steps:

[0018] S1, batching process: weigh the main material and auxiliary material according to the above proportion, add deionized water to the main material for sand grinding, and spray dry to obtain the spray material;

[0019] S2, pre-burning process: pre-burning the spray material to obtain pre-burned material;

[0020] S3, secondary sand grinding process: after adding auxiliary materials to the pre-burned material, add deionized water for secondary sand grinding to obtain secondary sand abrasive;

[0021] S4, spray granulation process: spray granulate the secondary sand abrasive to obtain manganese zinc ferrite granulated powder.

[0022] As a possible implementation scheme, in step S2, the pre-firing temperature of the pre-firing process is 800-950° C., and the pre-firing time is 2-5 hours.

[0023] As a possible implementation scheme, in step S3, the time of the secondary sand grinding process is controlled within 50 min to 90 min, and the particle size distribution is controlled within D50: 1.0 μm to 1.6 μm.

[0024] The third aspect of the present invention provides a manganese-zinc ferrite, which is a molded body obtained by sintering manganese-zinc ferrite granulated powder, wherein the manganese-zinc ferrite granulated powder includes a main material and an auxiliary material, the main material is composed of an iron compound, a zinc compound and a manganese compound, the iron compound is 52-55 mol% in terms of Fe2O3 conversion, the zinc compound is 19-22 mol% in terms of ZnO conversion, and the manganese compound is the remainder in terms of MnO conversion, the particle size of the auxiliary material is within 100 nm, and its composition includes four types of CaCO3, Co3O4, Nb2O5, and V2O5, wherein: CaCO3 accounts for 200ppm-1000ppm of the total weight of the main material, Co3O4 accounts for 500ppm-2000ppm of the total weight of the main material, Nb2O5 accounts for 100ppm-300ppm of the total weight of the main material, and V2O5 accounts for 100ppm-500ppm of the total weight of the main material.

[0025] When the above technical solution is adopted, the four auxiliary materials of the present invention have a synergistic effect with the main material:

[0026] The melting point of Nb2O5 is 1520℃. During the sintering process in ferrite, it mainly exists in the grain boundary. A small amount of addition can prevent the formation of large grains. The formed grains have good uniformity. Therefore, a small amount of Nb2O5 is added to make μ i However, when Nb2O5 is added in excess, it accumulates in the grain boundaries, which significantly reduces the grain size. As the amount of Nb2O5 added increases, grain growth is hindered and the grain size decreases, thereby reducing the magnetic domain width, increasing the domain wall resonance frequency, and improving its frequency characteristics.

[0027] CaCO3 mainly exists on the grain boundaries, thereby increasing the grain boundary resistivity. Co3O4 adjusts the magnetocrystalline anisotropy constant K1, making the material have good temperature stability and high magnetic permeability. 2+ Can inhibit Fe 2+ The combination of the two makes the material have a higher resistivity at high frequencies, thereby improving the impedance at high frequencies, and because the conductive electron migration of MnZn ferrite is mainly through Fe 2+ with Fe 3+ The electronic transition of Fe 2+ Reduce, the resistivity of ferrite increases, and the frequency characteristics will also be improved to a certain extent.

[0028] V2O5, as a low melting point metal oxide, exists in liquid form during high temperature sintering of ferrite particles. Therefore, adding an appropriate amount is beneficial to increase the contact area of ​​the solid phase reaction during the sintering process, accelerate the reaction rate, promote grain growth, and obtain a higher initial magnetic permeability. The above doping cooperates with each other and finally controls the Fe through a higher sintering temperature and a higher oxygen content. 2+ The production of this material enables it to achieve broadband and high permeability performance.

[0029] Nb2O5 exists on the grain boundaries, making the grains uniform, but V2O5, a low melting point substance, must be added simultaneously to speed up the reaction and promote grain growth. Otherwise, although the grains are uniform, they are small in size, resulting in a low initial magnetic permeability. Both CaCO3 and Co3O4 have the effect of increasing resistivity, but one increases the resistivity of the grain boundaries and the other increases the resistivity within the grains. The combination of the two makes the overall resistivity even greater, thereby maximizing the improvement of impedance at high frequencies.

[0030] As a possible implementation scheme, it is measured that the lattice particle size of the manganese-zinc ferrite in the microscopic state is close to the same, that is, the average particle size distribution of the grains inside the magnetic core is narrow, and the D10, D50, and D90 of the grains inside the magnetic core meet the following conditions: (D90-D10) / D50≤1.1. When the above technical scheme is adopted, the particle size of the auxiliary materials added in the present invention is within 100nm. This is because the specific surface area of ​​the auxiliary materials is large when the particle size is within 100nm, and the surface energy is correspondingly high; at the same time, the surface atoms of the nanoparticles have a large number of unsaturated bonds, have high chemical activity, and are very easy to combine with other atoms to reach a stable state, so the addition of nano auxiliary materials helps the grains of the manganese-zinc ferrite material to grow uniformly to an ideal size.

[0031] A fourth aspect of the present invention provides a method for preparing manganese-zinc ferrite, comprising the following steps:

[0032] S1, batching process: weigh the main material and auxiliary material according to the above proportion, add deionized water to the main material for sand grinding, and spray dry to obtain the spray material;

[0033] S2, pre-burning process: pre-burning the spray material to obtain pre-burned material;

[0034] S3, secondary sand grinding process: after adding auxiliary materials to the pre-burned material, add deionized water for secondary sand grinding to obtain secondary sand abrasive;

[0035] S4, spray granulation step: spray granulation of the secondary sand abrasive to obtain manganese zinc ferrite granulated powder;

[0036] S5, forming process: forming the manganese zinc ferrite granulated powder into a ring blank;

[0037] S6, sintering process: sinter the ring blank at 1300°C to 1380°C, and control the oxygen content of the atmosphere to 3% to 8%, thereby obtaining a wide-band high-permeability manganese-zinc ferrite material.

[0038] As a possible implementation scheme, in step S2, the pre-firing temperature of the pre-firing process is 800-950° C., and the pre-firing time is 2-5 hours.

[0039] As a possible implementation scheme, in step S3, the time of the secondary sand grinding process is controlled within 50 min to 90 min, and the particle size distribution is controlled within D50: 1.0 μm to 1.6 μm.

[0040] As a possible implementation scheme, in step S6, the sintering process is sintering in a staged variable speed temperature rise, and the sintering temperature variation curve is:

[0041] Raise the temperature from room temperature to 400-600°C at a rate of 2-4°C / min and keep warm for 2-4h;

[0042] Continue heating to 900-1100°C at a heating rate of 2-5°C / min;

[0043] Continue to heat up to 1300-1380°C at a heating rate of 1-3°C / min, and keep at 1300-1380°C for 4-8h;

[0044] After the insulation is completed, cool to room temperature at a rate of 2 to 5°C / min.

[0045] In the case of adopting the above technical solution, the granulated powder of the present invention is used in combination with a special sintering process to solve the problem that the magnetic permeability of high-permeability materials decreases too quickly at high frequencies, and broadband characteristics are achieved. In addition, due to the improvement of magnetic permeability at high frequencies, its impedance characteristics are also improved, so that the material has a stronger anti-electromagnetic interference ability. That is, the initial magnetic permeability of the manganese-zinc ferrite obtained by the present invention is greater than 5000, the magnetic permeability at 1MHz is greater than 3000, and the impedance Z of the T25 / 15 / 12 sample ring at 1MHz is greater than 42Ω.

[0046] The fifth aspect of the present invention provides an application of manganese-zinc ferrite for preparing power supply common-mode electromagnetic interference EMI filters, broadband transformers and inductor cores of digital communication systems, which play a good role in signal conversion and transmission.

[0047] 3. Beneficial effects

[0048] Compared with the prior art, the present invention has the following beneficial effects:

[0049] The manganese-zinc ferrite of the present invention has an initial magnetic permeability of more than 5000 and a magnetic permeability of more than 3000 at a frequency point of 1 MHz, and also has a relatively high impedance characteristic (the impedance Z of the sample ring of T25 / 15 / 12 at 1 MHz is greater than 42Ω), thereby having good anti-electromagnetic interference capability in a relatively wide frequency range. DETAILED DESCRIPTION

[0050] The present invention is further described below in conjunction with specific embodiments.

[0051] Example 1

[0052] A manganese-zinc ferrite of the present embodiment includes a main material and an auxiliary material. The main material is composed of an iron compound, a zinc compound and a manganese compound. The iron compound is 52.5 mol% in terms of Fe2O3 conversion, the zinc compound is 20 mol% in terms of ZnO conversion, and the manganese compound is the remainder in terms of MnO conversion. The particle size of the auxiliary material is all within 100 nm, and its composition includes four types: CaCO3, Co3O4, Nb2O5, and V2O5, wherein: CaCO3 accounts for 400 ppm of the total weight of the main material, Co3O4 accounts for 800 ppm of the total weight of the main material, Nb2O5 accounts for 200 ppm of the total weight of the main material, and V2O5 accounts for 150 ppm of the total weight of the main material.

[0053] A method for preparing a manganese-zinc ferrite granulated powder of this embodiment comprises the following steps:

[0054] S1, batching process: weigh the main material and auxiliary material according to the above proportion, add deionized water to the main material for sand grinding, and spray dry to obtain the spray material;

[0055] S2, pre-burning process: pre-burn the spray material, the pre-burning temperature is 800-950°C, the pre-burning time is 2-5 hours, and the pre-burned material is obtained;

[0056] S3, secondary sand grinding process: after adding auxiliary materials to the pre-burned material, add deionized water for secondary sand grinding, the time is controlled within 50min to 90min, and the particle size distribution is controlled within D50: 1.0μm to 1.6μm, to obtain secondary sand abrasive;

[0057] S4, spray granulation step: spray granulation of the secondary sand abrasive to obtain manganese zinc ferrite granulated powder;

[0058] S5, forming process: forming the manganese zinc ferrite granulated powder into a ring blank;

[0059] S6, sintering process: sinter the ring blank at 1380°C, and control the oxygen content of the atmosphere to 4.5%, so as to obtain the wide-band and high-permeability manganese-zinc ferrite material of this embodiment.

[0060] Among them, in the sintering process of step S6 of this embodiment, sintering is performed in a staged variable speed temperature rise, and the sintering temperature change curve is:

[0061] The temperature was raised from room temperature to 500°C at a rate of 3°C / min and kept at this temperature for 3 h;

[0062] Continue heating to 1000°C at a heating rate of 4°C / min;

[0063] Continue to increase the temperature to 1380°C at a rate of 2°C / min and keep at 1380°C for 6 hours;

[0064] After the insulation was completed, the mixture was cooled to room temperature at a rate of 3°C / min.

[0065] Example 2

[0066] A manganese-zinc ferrite of the present embodiment includes a main material and an auxiliary material. The main material is composed of an iron compound, a zinc compound and a manganese compound. The iron compound is 54 mol% calculated as Fe2O3, the zinc compound is 20 mol% calculated as ZnO, and the manganese compound is the remainder calculated as MnO. The particle size of the auxiliary material is less than 100 nm, and the composition includes four types of CaCO3, Co3O4, Nb2O5, and V2O5, wherein: CaCO3 accounts for 400 ppm of the total weight of the main material, Co3O4 accounts for 800 ppm of the total weight of the main material, Nb2O5 accounts for 200 ppm of the total weight of the main material, and V2O5 accounts for 150 ppm of the total weight of the main material.

[0067] A method for preparing a manganese-zinc ferrite granulated powder of this embodiment comprises the following steps:

[0068] S1, batching process: weigh the main material and auxiliary material according to the above proportion, add deionized water to the main material for sand grinding, and spray dry to obtain the spray material;

[0069] S2, pre-burning process: pre-burn the spray material, the pre-burning temperature is 800-950°C, the pre-burning time is 2-5 hours, and the pre-burned material is obtained;

[0070] S3, secondary sand grinding process: after adding auxiliary materials to the pre-burned material, add deionized water for secondary sand grinding, the time is controlled within 50min to 90min, and the particle size distribution is controlled within D50: 1.0μm to 1.6μm, to obtain secondary sand abrasive;

[0071] S4, spray granulation step: spray granulation of the secondary sand abrasive to obtain manganese zinc ferrite granulated powder;

[0072] S5, forming process: forming the manganese zinc ferrite granulated powder into a ring blank;

[0073] S6, sintering process: sinter the ring blank at 1370° C., and control the oxygen content of the atmosphere to 4.5%, thereby obtaining the wide-band and high-permeability manganese-zinc ferrite material of this embodiment.

[0074] Among them, in the sintering process of step S6 of this embodiment, sintering is performed in a staged variable speed temperature rise, and the sintering temperature change curve is:

[0075] The temperature was raised from room temperature to 500°C at a rate of 3°C / min and kept at this temperature for 3 h;

[0076] Continue heating to 1000°C at a heating rate of 4°C / min;

[0077] Continue to increase the temperature to 1370°C at a rate of 2°C / min and keep at 1370°C for 6 hours;

[0078] After the insulation was completed, the mixture was cooled to room temperature at a rate of 3°C / min.

[0079] Example 3

[0080] A manganese-zinc ferrite of the present embodiment includes a main material and an auxiliary material. The main material is composed of an iron compound, a zinc compound and a manganese compound. The iron compound is 52 mol% in terms of Fe2O3 conversion, the zinc compound is 22 mol% in terms of ZnO conversion, and the manganese compound is the remainder in terms of MnO conversion. The particle size of the auxiliary material is all within 100 nm, and its composition includes four types: CaCO3, Co3O4, Nb2O5, and V2O5, wherein: CaCO3 accounts for 400 ppm of the total weight of the main material, Co3O4 accounts for 800 ppm of the total weight of the main material, Nb2O5 accounts for 200 ppm of the total weight of the main material, and V2O5 accounts for 150 ppm of the total weight of the main material.

[0081] A method for preparing a manganese-zinc ferrite granulated powder in this embodiment comprises the following steps:

[0082] S1, batching process: weigh the main material and auxiliary material according to the above proportion, add deionized water to the main material for sand grinding, and spray dry to obtain the spray material;

[0083] S2, pre-burning process: pre-burn the spray material, the pre-burning temperature is 800-950°C, the pre-burning time is 2-5 hours, and the pre-burned material is obtained;

[0084] S3, secondary sand grinding process: after adding auxiliary materials to the pre-burned material, add deionized water for secondary sand grinding, the time is controlled within 50min to 90min, and the particle size distribution is controlled within D50: 1.0μm to 1.6μm, to obtain secondary sand abrasive;

[0085] S4, spray granulation step: spray granulation of the secondary sand abrasive to obtain manganese zinc ferrite granulated powder;

[0086] S5, forming process: forming the manganese zinc ferrite granulated powder into a ring blank;

[0087] S6, sintering process: sinter the ring blank at 1370° C., and control the oxygen content of the atmosphere to 4.5%, thereby obtaining the wide-band and high-permeability manganese-zinc ferrite material of this embodiment.

[0088] Among them, in the sintering process of step S6 of this embodiment, sintering is performed in a staged variable speed heating process, and the sintering temperature variation curve is:

[0089] The temperature was raised from room temperature to 500°C at a rate of 3°C / min and kept at this temperature for 3 h;

[0090] Continue heating to 1000°C at a heating rate of 4°C / min;

[0091] Continue to increase the temperature to 1370°C at a rate of 2°C / min and keep at 1370°C for 6 hours;

[0092] After the insulation was completed, the mixture was cooled to room temperature at a rate of 3°C / min.

[0093] Example 4

[0094] A manganese-zinc ferrite of the present embodiment includes a main material and an auxiliary material. The main material is composed of an iron compound, a zinc compound and a manganese compound. The iron compound is 52.5 mol% in terms of Fe2O3 conversion, the zinc compound is 20 mol% in terms of ZnO conversion, and the manganese compound is the remainder in terms of MnO conversion. The particle size of the auxiliary material is all within 100 nm, and its composition includes four types: CaCO3, Co3O4, Nb2O5, and V2O5, wherein: CaCO3 accounts for 400 ppm of the total weight of the main material, Co3O4 accounts for 800 ppm of the total weight of the main material, Nb2O5 accounts for 200 ppm of the total weight of the main material, and V2O5 accounts for 150 ppm of the total weight of the main material.

[0095] A method for preparing a manganese-zinc ferrite granulated powder of this embodiment comprises the following steps:

[0096] S1, batching process: weigh the main material and auxiliary material according to the above proportion, add deionized water to the main material for sand grinding, and spray dry to obtain the spray material;

[0097] S2, pre-burning process: pre-burn the spray material, the pre-burning temperature is 800-950°C, the pre-burning time is 2-5 hours, and the pre-burned material is obtained;

[0098] S3, secondary sand grinding process: after adding auxiliary materials to the pre-burned material, add deionized water for secondary sand grinding, the time is controlled within 50min to 90min, and the particle size distribution is controlled within D50: 1.0μm to 1.6μm, to obtain secondary sand abrasive;

[0099] S4, spray granulation step: spray granulation of the secondary sand abrasive to obtain manganese zinc ferrite granulated powder;

[0100] S5, forming process: forming the manganese zinc ferrite granulated powder into a ring blank;

[0101] S6, sintering process: sinter the ring blank at 1370°C, and control the oxygen content of the atmosphere to 3.1%, so as to obtain the wide-band and high-permeability manganese-zinc ferrite material of this embodiment.

[0102] Among them, in the sintering process of step S6 of this embodiment, sintering is performed in a staged variable speed temperature rise, and the sintering temperature change curve is:

[0103] The temperature was raised from room temperature to 500°C at a rate of 3°C / min and kept at this temperature for 3 h;

[0104] Continue heating to 1000°C at a heating rate of 4°C / min;

[0105] Continue to increase the temperature to 1370°C at a rate of 2°C / min and keep at 1370°C for 6 hours;

[0106] After the insulation was completed, the mixture was cooled to room temperature at a rate of 3°C / min.

[0107] Example 5

[0108] This embodiment is basically the same as embodiment 1, except that in step S6, the sintering process is sintering at a constant temperature rise rate, that is, the temperature is raised from room temperature to 1380°C at a temperature rise rate of 2°C / min, and kept at 1380°C for 6 hours, which is not conducive to debinding and densification.

[0109] Comparative Example 1

[0110] This comparative example is basically the same as Example 1, except that Nb2O5 accounts for 400ppm of the total weight of the main material.

[0111] Comparative Example 2

[0112] This comparative example is basically the same as Example 1, except that it does not contain CaCO3.

[0113] Comparative Example 3

[0114] This comparative example is basically the same as Example 1, except that it does not contain Co3O4.

[0115] Comparative Example 4

[0116] This comparative example is basically the same as Example 1, except that it does not contain V2O5.

[0117] Comparative Example 5

[0118] This comparative example is basically the same as Example 1, except that: S6, sintering process: the ring blank is sintered at 1390°C, and the sintering temperature change curve is as follows during the stepwise variable speed heating:

[0119] The temperature was raised from room temperature to 500°C at a rate of 3°C / min and kept at this temperature for 3 h;

[0120] Continue heating to 1000°C at a heating rate of 4°C / min;

[0121] Continue to heat up to 1390°C at a rate of 2°C / min and keep at 1390°C for 6 hours;

[0122] After the insulation was completed, the mixture was cooled to room temperature at a rate of 3°C / min.

[0123] In this comparative example, the high sintering temperature increased the magnetic permeability, but the frequency characteristics were insufficient.

[0124] Comparative Example 6

[0125] This comparative example is basically the same as Example 1, except that: S6, sintering process: sintering the ring blank at 1370° C. in a nitrogen atmosphere.

[0126] The magnetic permeability and impedance of the manganese-zinc ferrite materials obtained in various embodiments and comparative examples under broadband conditions are shown in Table 1:

[0127] Table 1 Performance test of manganese-zinc ferrite obtained in each embodiment and comparative example

[0128]

[0129] It can be seen from Table 1 that the initial magnetic permeabilities of Examples 1 to 5 are all greater than 5000. As the frequency increases, the magnetic permeabilities can still reach greater than 3000 at 1 MHz. At the same time, the impedance Z of the sample ring T25 / 15 / 12 at 1 MHz is greater than 42Ω; in Comparative Example 1, the Nb2O5 content accounts for more than 200ppm of the total weight of the main material, and Comparative Examples 2 / 3 / 4 lack CaCO3, Co3O4, and V2O5 respectively. Although the initial magnetic permeability is higher than 5000, the magnetic permeability at 1 MHz is lower than 3000. The insulation temperature in the sintering process of Comparative Example 5 is increased by 10°C relative to that of Example 1. Although the initial magnetic permeability is high, the magnetic permeability at 1 MHz is lower than 3000; Comparative Example 6 does not contain an oxygen atmosphere, and the magnetic permeability and impedance are relatively low. At the same time, the internal lattice size distribution of the ferrite in the comparative example is relatively wide, which affects the magnetic permeability and impedance performance.

[0130] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art. The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiments according to the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A manganese-zinc ferrite granulated powder, characterized in that: The invention comprises a main material and auxiliary materials, wherein the main material is composed of an iron compound, a zinc compound and a manganese compound, wherein the iron compound is 52 to 55 mol% in terms of Fe2O3 conversion, the zinc compound is 19 to 22 mol% in terms of ZnO conversion, and the manganese compound is the remainder in terms of MnO conversion. The particle sizes of the auxiliary materials are all within 100 nm, and the composition comprises four kinds of materials, namely, CaCO3, Co3O4, Nb2O5 and V2O5, wherein: CaCO3 accounts for 200ppm to 1000ppm of the total weight of the main material, Co3O4 accounts for 500ppm to 2000ppm of the total weight of the main material, Nb2O5 accounts for 100ppm to 300ppm of the total weight of the main material, and V2O5 accounts for 100ppm to 500ppm of the total weight of the main material.

2. The manganese-zinc ferrite granulated powder according to claim 1, characterized in that: The weight ratio of CaCO3, Co3O4, Nb2O5 and V2O5 in the auxiliary materials is 8:16:4:

3.

3. The manganese-zinc ferrite granulated powder according to claim 1, characterized in that: In the main material, the molar ratio of Fe2O3 and ZnO is 21:

8.

4. A method for preparing the manganese-zinc ferrite granulated powder according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, batching process: adding deionized water to the main material for sand grinding, and spray drying to obtain spray material; S2, pre-burning process: pre-burning the spray material to obtain pre-burned material; S3, secondary sand grinding process: after adding auxiliary materials to the pre-burned material, add deionized water for secondary sand grinding to obtain secondary sand abrasive; S4, spray granulation process: spray granulate the secondary sand abrasive to obtain manganese zinc ferrite granulated powder.

5. The method for preparing a manganese-zinc ferrite granulated powder according to claim 4, characterized in that: In step S2, the pre-firing temperature of the pre-firing process is 800 to 950°C, and the pre-firing time is 2 to 5 hours.

6. The method for preparing a manganese-zinc ferrite granulated powder according to claim 4, characterized in that: In step S3, the time of the secondary sand grinding process is controlled within 50 min to 90 min, and the particle size distribution is controlled within D50: 1.0 μm to 1.6 μm.

7. A manganese-zinc ferrite, characterized in that: A molded body obtained by sintering the manganese-zinc ferrite granulated powder as described in any one of claims 1 to 3, wherein D10, D50, and D90 of the grains inside the magnetic core meet the following conditions: (D90-D10) / D50≤1.

1.

8. A method for preparing manganese-zinc ferrite, characterized in that: The granulated powder obtained by the preparation method of manganese-zinc ferrite granulated powder according to claims 4 to 6 is subjected to a molding process and a sintering process to obtain a manganese-zinc ferrite material, wherein: the sintering process is: sintering the molded granulated powder at 1300°C to 1380°C, wherein the oxygen content of the atmosphere is controlled at 3% to 8%.

9. The method for preparing manganese-zinc ferrite according to claim 7, characterized in that: The sintering process is staged variable speed heating sintering, and the sintering temperature change curve is: Raise the temperature from room temperature to 400-600°C at a rate of 2-4°C / min and keep warm for 2-4h; Continue heating to 900-1100°C at a heating rate of 2-5°C / min; Continue to heat up to 1300-1380°C at a heating rate of 1-3°C / min, and keep at 1300-1380°C for 4-8h; After the insulation is completed, cool to room temperature at a rate of 2 to 5°C / min.

10. Use of the manganese-zinc ferrite according to claim 7 in preparing filters, broadband transformers, and inductor cores.

Citation Information

Patent Citations

  • Method for manufacturing broadband high-conductivity manganese-zinc ferrite magnetic core

    CN102360916B

  • Broadband high-permeability high-impedance manganese-zinc ferrite and preparation method thereof

    CN112142457A

  • Method for manufacturing broadband high-conductivity manganese-zinc ferrite magnetic core

    CN102360916A

  • High-cutoff-frequency high-conductivity manganese zinc ferrite material and production method thereof

    CN106747395A

  • Mn-Zn ferrite material with high using frequency, high permeability and high impedance

    CN109485404A